PT Bumi Suksesindo Corporate Social Responsibility Grows New Entrepreneurs - Zainal Abidin; Rimi Gusliana Mais (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
Micro, small and medium enterprises (MSMEs) occupy a strategic position in Indonesia, not only regarding economic growth but also on equal distribution of income in society. In various crisis conditions, the resilience of MSMEs has been tested. The Indonesian government always pays special attention to this business group through multiple departments or ministries. Apart from the government, the private sector also pays great attention to multiple levels of MSME development through corporate social responsibility (CSR) programs. This study aims to explore and elaborate on PT BumiSuksesindo's CSR programs in fostering new entrepreneurs. The analysis was carried out on six in-depth interviews with beneficiaries/groups of beneficiaries. These findings indicate that the company's CSR program is a charity program (donation) and empowerment (empowerment). The benefits of the BSI CSR program are also manifested in forming new entrepreneurs. The implications of this research can be taken into account by stakeholders to continue the program to foster new entrepreneurs in the operating locations..